Modelación de la cinética de degradación de alimentos para rumiantes (2007)
ABSTRACT: The in situ degradation technique has been adopted to evaluate the rate and extent of ruminal food degradation. The new models for formulation and evaluation of foods require of the precise determination of the dynamic aspects of ruminal foods degradation for which the in situ technique has been adopted in order to facilitate its mathematical determination. Different sources of variation related with the technique itself can alter the rate and extent of food degradation: the size of nylon bag, pore size, specific placement of the bag into the rumen, particle size of food and the mathematical models used for analyses, among others. Different models have been proposed for degradation kinetic studies. In these models the characteristics of food samples, anatomical and physiologic aspects of the animal, as well as those processes related with the hydrate and colonization of samples by ruminal microorganism have been considered. The objective of this work was to discuss some of the models used to evaluate the rate and extent of food degradation in the rumen by the mathematical description and practical application of the in situ technique.